Sentiment Analysis of Statement using Natural Language Processing - Meshram, Sayali; Balani, Nisha; Jha, Parul (International Journal of Computer Sciences and Engineering, 2025)
Sentiment analysis is one of the fastest growing research areas in computer science, making it challenging to keep track of all the activities in the area. Sentiment analysis is a technology with great practical value; it can solve the phenomenon of network comment information disorderly to a certain extent, and accurate positioning of user information required. Internet has opened the new doors for information exchange and the growth of social media has created unprecedented opportunities for citizens to publicly raise their opinions, but it has serious bottlenecks when it comes to do analysis of these opinions. Even urgency to gain a real time understanding of citizens concerns has grown very rapidly. Since, the viral nature of social media which is fast and distributed one, some issues get rapidly distributed and unpredictably become important through this word of mouth opinions expressed online which in turn has known as sentiments of the users. The decision makers and people do not yet realized to make sense of this mass communication and interact sensibly with thousands of others with the help of sentiment analysis.